2017
DOI: 10.1111/bcp.13288
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral antidiabetic agents and risk of community‐acquired pneumonia: a nested case–control study

Abstract: No differences in the incidence of CAP were observed between the use of OAD in monotherapy vs. metformin. Thiazolidinedione use in combination was associated with an increase in the risk of CAP when compared to metformin + sulfonylureas. The use of DPP-4 inhibitors was not associated with an increased risk of CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
(27 reference statements)
1
39
0
5
Order By: Relevance
“…The last lane reports the final estimate for all molecules found that DPP-4 inhibitors exerted no protection against pneumonia. 28 Pooling those two literature studies with our findings led to inconclusive results, as the overall RR of pneumonia associated with DPP-4 inhibitors was not significantly different from 1.0. It is important to note that both the study by Wvan der Zanden et al 27 and the current study were cohort studies and provide essentially superimposable results, whereas the study by Gorricho et al 28 was a nested case control study.…”
Section: Discussionmentioning
confidence: 49%
“…The last lane reports the final estimate for all molecules found that DPP-4 inhibitors exerted no protection against pneumonia. 28 Pooling those two literature studies with our findings led to inconclusive results, as the overall RR of pneumonia associated with DPP-4 inhibitors was not significantly different from 1.0. It is important to note that both the study by Wvan der Zanden et al 27 and the current study were cohort studies and provide essentially superimposable results, whereas the study by Gorricho et al 28 was a nested case control study.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have raised concerns about the safety of antihyperglycemic combination therapies in relation to diabetes-related outcomes such as hypoglycemia [ 40 ], cardiovascular events and mortality [ 41 ], and microvascular complications [ 42 ]. However, recent studies have also focused on some less-known safety issues related to multiple drug use, including dementia [ 43 ], fracture risk [ 44 ], and community-acquired pneumonia [ 45 ]. Our findings suggest that undernutrition is another condition that can be found more frequently in older adults with T2DM requiring multiple antihyperglycemics.…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies examining the risk of DPP4 inhibitors and infections have examined all-cause infections 12 , upper respiratory tract infections 13 ,or pneumonia 18,19,48 as outcomes of interest. Similarly, the majority of meta-analysis pooling results from clinical trials suggest that there is not a significant risk of all-cause infection, upper respiratory tract infections, or pneumonia associated with using a DPP4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis pooling these trials did not find a difference in the rate of respiratory tract infections between users of DPP4 inhibitors and other agents 17 ; however, the included trials were of short duration and not designed to assess long-term safety. Recent observational studies have also failed to show any relationship between DPP4 inhibitors and community-acquired pneumonia 18,19 .…”
Section: Introductionmentioning
confidence: 99%